Yoga as atoolfor development of the future high moral civilization - Lobas, Viktoria (NTU "KhPI", 2018)
In this paper the author outlines the bullet points of modern societywith its value system. The globalization phenomena connected to information society leads to gradual integration of various cultures and religions. The practice of Yoga is well accepted and appreciated by modern human being. That leads to a conclusion, that Yoga Philosophy and Vedanta are necessary and have to be adopted into daily life of each individual to develop future high moral civilization and to increase the life quality of the population.

В цій статті автор змальовує основні пункти сучасного суспільства і його систему цінностей. Явища глобалізації, пов'язані з інформаційним суспільством, призводять до поступової інтеграції різних культур і релігій. Виходячи із спостережень і існуючих досліджень, практика Йоги цінується сучасною людиною. Це призводить до висновку, що Філософія Йоги і Веданта потрібні і мають бути впроваджені в повсякденне життя кожної людини, щоб розвинути майбутню високу моральну цивілізацію і збільшити якість життя її населення.
Йога як інструмент для розвитку майбутньої високоморальної цивілізації
Keywords: Yoga Philosophy; Vedanta; high moral civilization; future society; human; mindfulness; філософія йоги; Веданта; цивілізація високоморальна; суспільство майбутнє; людина; усвідомленність